International linkage of the Russian market and the Russian financial crisis: a multivariate GARCH analysis - Kashif Saleem (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
This study considers the linkage of the Russian equity market to the world market, examin-ing the international transmission of the Russia's 1998 financial crisis utilizing the GARCH-BEKK model proposed by Engle and Kroner (1995). We find evidence of direct linkage between the Russian equity market and the world markets with regards to returns and volatility. While the weakness of the linkage suggests that the Russian equity market was only partially integrated into the world market at the time of the crisis, evidence of contagion is clear.
URN:NBN:fi:bof-201408072088
Keywords: C32; G15; 330; Multivariate GARCH; Volatility spillovers; Russian Financial crisis; contagion; partial integration